Hadith Forgery and Zandaqah in Early Islamic History: Scholarly and Political Responses - Syanando Adzikri; Muhid Muhid (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study examines the influence of the Zindiq sect on the development of hadith studies in the 2nd century Hijri. The Zindiq sect systematically fabricated hadiths, distorted Islamic teachings, and raised doubts about the authenticity of hadith as a source of Islamic law. This research aims to analyze hadith from the perspective of the Zindiq sect, their impact, and the responses of hadith scholars and the government at that time in addressing their influence. Using a historical approach and qualitative methods, this study explores hadith falsification, the scholars' efforts in hadith criticism, and governmental actions against the Zindiq. The findings indicate that the Zindiq movement posed a serious challenge to hadith transmission and used it as a tool for their conspiracy, prompting scholars to refine hadith verification methods. Additionally, their activities accelerated the codification of hadith and the implementation of stricter transmission standards. This study concludes that although the Zindiq posed a significant threat to Islamic scholarship, they inadvertently contributed to the strengthening of hadith sciences. Further research is needed to explore the influence of other ideologies on hadith transmission.